An unusual case of aortic rupture after deployment of a bare stent in the treatment of aortic dissection in a patient with giant-cell arteritis - Rynio, Pawel (Wideochir Inne Tech Maloinwazyjne, 2017)
Giant-cell arteritis is associated with a higher risk of aortic aneurysm and aortic dissection formation. We present a women with aortic dissection type B treated with a stent graft and bare-metal stent implantation. After the stent deployment we noticed aortic rupture, which was successfully treated with implantation of an additional stent graft. This report highlights the difficulty of endovascular therapy in patients with giant-cell arteritis. We have to bear in mind that chronic inflammation of the aorta leads to a more fragile aortic wall than normal. We recommend the use of a stent graft over a bare-metal stent and gentle use of a balloon catheter.